uN2CpolyG-mediated p65 nuclear sequestration suppresses the NF-κB-NLRP3 pathway in neuronal intranuclear inclusion disease - Yu Shen; Kaiyan Jiang; Dandan Tan; Min Zhu; Yusen Qiu; Pencheng Huang; Wenquan Zou; Jianwen Deng; Zhaoxia Wang; Ying Xiong; Daojun Hong (Cell Communication and Signaling)
Abstract Background Neuronal intranuclear inclusion disease (NIID) is genetically linked to CGG repeat expansion in the 5’-untranslated region of the NOTCH2NLC gene, with nascent polyglycine-containing protein (uN2CpolyG) identified as a primary pathogenic factor. Emerging clinical evidence suggests that inflammation contributes to NIID pathogenesis, yet the underlying molecular mechanisms remain elusive. This study aimed to elucidate the molecular interaction between uN2CpolyG and the NF-κB-NLRP3 pathway. Methods Single-cell RNA sequencing was conducted on the skin tissues of NIID patients to assess changes in the expression of genes involved in inflammatory pathways. Cell models (HEK-293T and U87-MG) transfected with CGG9/69/100 expansion vectors were used to investigate alterations in the NF-κB-NLRP3-autophagy pathway. Additionally, the therapeutic potential of NF-κB activators was evaluated in a Drosophila model with a CGG expansion knock-in. Results Single-cell sequencing revealed a significant reduction in the expression of NFKBIA, encoding NF-κB inhibitor alpha (IkBa), which facilitates the nuclear translocation of p65, a key NF-κB component. uN2CpolyG directly interacted with and sequestered p65 in nuclear inclusions, leading to reduced phosphorylated p65 (p-p65) levels. This sequestration significantly downregulated the NF-κB-NLRP3 pathway, impairing autophagy, as indicated by decreased LC3II/LC3I ratios. Treatment of CGG100 cells with lipopolysaccharide (LPS) significantly increased p-p65, NLRP3, and LC3II/LC3I levels while reducing insoluble uN2CpolyG levels and intranuclear inclusions. In the Drosophila knock-in model, LPS significantly reduced the number of intranuclear inclusions and improved phenotypic manifestations. Conclusions This study revealed that uN2CpolyG directly interacts with and sequesters p65, thereby inhibiting the NF-κB-NLRP3 pathway and impairing autophagy. This mechanism highlights a novel therapeutic target for NIID and provides potentially broader insights into similar mechanisms in other neurodegenerative diseases characterized by misfolded protein aggregates.